Analytical and Numerical Research of Temperature Fields in Cylindrical Thermocouple with Internal Heat Sources - Ivanochko, M.M.; Ivanushchak, N.M.; Struk, A.Ya. (Journal of Thermoelectricity, 2025)
The method of finite integral transformations has been used to analytically solve the problem of unsteady thermal conductivity of a confined cylinder with continuously operating heat sources placed in a medium with a constant temperature. An approach for numerical investigation of thermal fields in cylindrical structures with internal heat sources, taking into account the influence of external conditions, has been proposed. The analytical solution has been numerically implemented, the heat distribution has been numerically simulated, and the thermodynamic behavior of the system has been 3D visualized. The numerical modeling technique has been used to predict the temperature regime in thermoelectric structures with internal heat sources, which is the basis for the engineering design of efficient thermoelectric systems.